Pelatihan Pengembangan Bahan Ajar Sains Tematik Terintegrasi Literasi Baru Bagi Guru IPA - Asrizal Asrizal; Festiyed Festiyed; Yurnetti Yurnetti (Jurnal Pemberdayaan Masyarakat, 2023)
Learning should be able to develop students' new literacy to answer challenges in the 4.0 industrial revolution. But science teachers still have difficulty creating learning that is relevant to this era. The solution to the problem is to train science teachers to develop thematic science learning material integrated with new literacy. The objective of the training is to investigate the results of training on the development of thematic science learning material integrated with new literacy. The method of training is demonstration and example by instructors. The training stages include assessing needs, setting goals, designing program, implementing activities, and evaluating training activities. Based on the implementation of the training, it can be stated that science teachers have been able to produce examples of new literacy integrated thematic science learning material in the form of student worksheet, the validity value of thematic science learning material can be classified into the good category, and generally they feel the benefits of training in the material aspects of developing learningÂ  material, thematic learning material, integration of new literacy, and writing of thematic science learningÂ  material. Thus, the training activity has been able to promote science teachers in planning and developing thematic science learning material.